PET Imaging of Neurofibromatosis Type 1 with a Fluorine-18 Labeled Tryptophan Radiotracer - Xuyi Yue; Erik Stauff; Shriya Boyapati; Sigrid A. Langhans; Wenqi Xu; Sokratis Makrogiannis; Uchenna J. Okorie; Azubuike M. Okorie; Vinay V. R. Kandula; Heidi H. Kecskemethy; Rahul M. Nikam; Lauren W. Averill; et al. (MDPI AG, 2024)
Neurofibromatosis type 1 (NF1) is a neurocutaneous disorder. Plexiform neurofibromas (PNFs) are benign tumors commonly formed in patients with NF1. PNFs have a high incidence of developing into malignant peripheral nerve sheath tumors (MPNSTs) with a 5-year survival rate of only 30%. Therefore, the accurate diagnosis and differentiation of MPNSTs from benign PNFs are critical to patient management. We studied a fluorine-18 labeled tryptophan positron emission tomography (PET) radiotracer, 1-(2-[18F]fluoroethyl)-L-tryptophan (L-[18F]FETrp), to detect NF1-associated tumors in an animal model. An ex vivo biodistribution study of L-[18F]FETrp showed a similar tracer distribution and kinetics between the wild-type and triple mutant mice with the highest uptake in the pancreas. Bone uptake was stable. Brain uptake was low during the 90-min uptake period. Static PET imaging at 60 min post-injection showed L-[18F]FETrp had a comparable tumor uptake with [1⁸F]fluorodeoxyglucose (FDG). However, L-[18F]FETrp showed a significantly higher tumor-to-brain ratio than FDG (n = 4, p < 0.05). Sixty-minute-long dynamic PET scans using the two radiotracers showed similar kidney, liver, and lung kinetics. A dysregulated tryptophan metabolism in NF1 mice was further confirmed using immunohistostaining. L-[18F]FETrp is warranted to further investigate differentiating malignant NF1 tumors from benign PNFs. The study may reveal the tryptophan-kynurenine pathway as a therapeutic target for treating NF1.